Around the world in eighty days and five weeks in a balloon - Verne, Jules (Wordsworth Edition Hertfordshire, 2002)
The story of the journey made by a Victorian gentleman, Phileas Fogg, who wagered that he could travel around the world in eighty daysFive weeks in a balloon was Verne's first novel, which documents a jaunt across Africa in a hydrogen balloonm